Islamic Banking and Finance: Book Review - Mutia Risma Ma'rufi (Journal of Islamic Studies and Education, 2024)
"Islamic Banking and Finance: Second Edition" by Zubair Hasan provides an in-depth exploration of the principles, practices, and theoretical underpinnings of Islamic finance. This book will be published in 2023. The book delves into the fundamental concepts of Shariah-compliant banking, offering a comprehensive overview of the prohibition of interest (riba), the importance of risk-sharing, and the promotion of ethical investments. Hasan meticulously explains various Islamic financial instruments such as mudarabah, musharakah, ijara, and sukuk, making the book an essential resource for understanding how Islamic banking operates differently from conventional financial systems. According to Čihák & Hesse (2010), these financial instruments are This is the fundamental principle in Islamic banking. Besides, the primary audience for this book includes students, academics, and professionals in the fields of finance, economics, and Islamic studies.